Patient engagement practice within perinatal eHealth: A scoping review - Auxier Jennifer N; Bender Miriam; Hakojarvi Henna-Riikka; Axelin Anna M (WILEY, 2025)
Background: There is a gap in knowledge about how perinatal eHealth programs function to support autonomy for new and expectant parents from pursuing wellness goals.
Objectives: To examine patient engagement (access, personalization, commitment and therapeutic alliance) within the practice of perinatal eHealth.
Design: Scoping review.
Methods: Five databases were searched in January 2020 and updated in April 2022. Reports were vetted by three researchers and included if they documented maternity/neonatal programs and utilized World Health Organization (WHO) person-centred digital health intervention (DHI) categories. Data were charted using a deductive matrix containing WHO DHI categories and patient engagement attributes. A narrative synthesis was conducted utilizing qualitative content analysis. Preferred Reporting Items for Systematic Reviews and Meta-Analyses 'extension for scoping reviews' guidelines were followed for reporting.
Results: Twelve eHealth modalities were found across 80 included articles. The analysis yielded two conceptual insights: (1) The nature of perinatal eHealth programs: (1) emergence of a complex structure of practice and (2) practising patient engagement within perinatal eHealth.
Conclusion: Results will be used to operationalize a model of patient engagement within perinatal eHealth.